2020
DOI: 10.1007/s13197-020-04436-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-assisted virgin coconut oil based extraction for maximizing polyphenol recovery and bioactivities of mangosteen peels

Abstract: Virgin coconut oil (VCO) and propylene glycol (PG) have received more attention as bio-based solvents for natural bioactive recovery in green extraction process.Here, maceration extraction and ultrasound-assisted extraction (UAE) of bioactive phenolics from mangosteen peel (MP) by VCO, PG and VCO-PG mixture were compared. The goal was to maximize the phenolic extraction and improve bioactivities. Based on a single-factor experiment for UAE with VCO, the optimal condition was sample to solvent ratio of 1:6.6 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The optimum conditions for acid hydrolysis were solid to solvent ratio of 1:50 g/mL, pH of 2, extraction temperature of 80 °C, and extraction time of 2 h; the best extraction yield was 3.09 ± 0.077%. This yield was close to that of Mohammed et al (2019) with microwave-assisted ethanol extraction, and was higher than Muzykiewicz et al (2020) with ultrasound-assisted extraction and Sungpud et al (2020) with virgin coconut oil (VCO) extraction [ 17 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 84%
“…The optimum conditions for acid hydrolysis were solid to solvent ratio of 1:50 g/mL, pH of 2, extraction temperature of 80 °C, and extraction time of 2 h; the best extraction yield was 3.09 ± 0.077%. This yield was close to that of Mohammed et al (2019) with microwave-assisted ethanol extraction, and was higher than Muzykiewicz et al (2020) with ultrasound-assisted extraction and Sungpud et al (2020) with virgin coconut oil (VCO) extraction [ 17 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 84%
“…The oil color is clear (colorless), slightly runny, the smell tends to be fresh coconut, and the amount of blondo (protein) is medium. In addition, the more solvent, the more oil is extracted [23]. In this study, the volume control of coconut milk was used, namely 500 mL, so that it affected the volume and yield of VCO obtained Based on Figure 1, it can be seen that four plastic cups show the results of VCO insulation with different colors.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, heating was carried out at 60C -70C for 20 minutes. According to Nely et al in their research, it was stated that the higher the temperature, the higher the temperature, the higher the emulsion stability, and the lower the yield of VCO obtained [23]. And suppose you look at the microscopic structure of the coconut milk emulsion with the heating method as shown in Figure 6.…”
Section: Heating Methodsmentioning
confidence: 99%
“…However, the vegetable oil is a mixed solvent, which is not easy to volatilize and separate. At the same time, the selectivity is not high enough, and it is difficult to extract the substances with strong polar substances and large molecular weight, It is usually necessary to introduce the entrainer containing polar group [26]. In the extraction experiment of polyphenols from mangosteen pericarp, based on the single factor experiment of natural coconut oil and ultrasonic assisted extraction, it was found that when the ratio of sample to solvent was 1:6.6g/ml, the amplitude was 55μm.…”
Section: Auxiliary Extraction Of Vegetable Oilmentioning
confidence: 99%